PENGARUH GAYA KEPEMIMPINAN KEPALA DESA TERHADAP MOTIVASI KERJA PERANGKAT DESA CIKANDE KECAMATAN SAGULING KABUPATEN BANDUNG BARAT - Supriadi, Ayi; Setia Budi, Warjum; Darussalam, Rian Syaefullah (Universitas Jenderal Ahmad Yani, 2025)
The research aims to analyze the influence of the Village Head's leadership style on the work motivation of Cikande Village officials, Saguling District, West Bandung Regency. The research focuses on the influence of the village head's leadership style and the work motivation of village officials. Descriptive research method with a quantitative approach that describes the village head's leadership style on work motivation in Cikande Village. The population in this study were all officials at the Cikande Village Office with a sampling technique using saturated sampling. Based on the results of statistical data analysis of the model summary table, the correlation value is 0.633. The large influence of the leadership style variable (X) on the work motivation variable (Y) is shown by the R Square value of 0.385 or 38.5%, the large influence of the independent variable or leadership style on the dependent variable work motivation (Y). Based on the results of the Anova statistical data analysis used to determine a simple regression equation model, it is known that the Fcount value g = 25.441 with a significance level of 0.000 is less than <0.05, so the leadership style variable (X) influences the work motivation variable (Y). This proves that Ha is accepted and H0 is rejected, namely the village head's leadership style influences the work motivation of officials in Cikande Village, Saguling District, West Bandung Regency.